Blogueros, derechos de autor y algunas otras cuestiones legales - Alla Kyryliuk; Viktoriia Lysenko; Alina Podolieva (Ius Humani. Jornal do direito, 2020)
The purpose of the study is to find out the place of the blog in the field of copyright; identification the most pressing problems that may arise as a result of blogging; and finding the most effective approaches and options to solve the above problems. The object of research is the system of national and foreign legislation, legal doctrine, bills in the field of intellectual property, and copyright. Empirical methods such as observation and description and theoretical methods such as analysis, synthesis, generalization, and explanation were used in this work. The work has the following structure: first, it takes care of the differences in understanding of copyright regulation in different legal systems, the world experience in regulating intellectual property, and its history. Then, blog copyrights are analyzed, as well as online copyright infringement, ways to protect content, and some other actual realities. As a result of the study of the intellectual property legislation that governs this subject—in particular, in the field of copyright and related rights—there is a clarification of the notion of “blog” and the regulation that governs blogging in Ukraine is identified. In addition, some practical recommendations were given to bloggers on legal protection of their copyrights.